Investigating Dental Care Patient Satisfaction in DSC Dental Clinic: A Case Study - Natalia Ika Wibisono; Jacob Donald Tan (Eduvest - Journal of Universal Studies, 2025)
Dental care plays a vital role in overall health, as poor oral health is linked to systemic diseases such as diabetes, cardiovascular issues, and malnutrition. In Indonesia, around 70% of the population experiences oral diseases, yet only 12% seek professional treatment, a figure significantly lower than the global average. This highlights the urgency of examining patient satisfaction in dental care. This study investigates patient satisfaction at DSC Dental Clinic in Surabaya, Indonesia, using a qualitative case study approach. Nine participants who received various dental treatments were interviewed through semi-structured methods and observed directly. The findings reveal that high clinical skills, clear communication, stringent infection control protocols, and a fair price-to-value perception contribute positively to patient satisfaction. However, inefficient administrative services negatively affect the patient experience. These insights can guide better collaboration between clinical and administrative staff to enhance the quality of dental care services. Furthermore, this research supports clinic management and policymakers in regulating private dental practices by ensuring strict hygiene standards, transparent pricing, and effective administrative procedures.